Transformation of River Restoration Movement Network - Zunariyah, Siti; ., Suharko; ., Suharman (KnE Social Sciences, 2023)
A study on social network transformation of river restoration movement is very important as it is related to the network’s ability of adapting to various changes and a movement’s sustainability. This research aims to reveal the history of movement emergence, tactic, and strategy, process and procedure of social network establishment and social network transformation. An ethnographic approach was chosen by involving Komunitas Pemerti Kali Code (Code River Observer Community) as the main subject of current research. Data collection was conducted through live-in-society process for 2 months to conduct participant observation, in-depth interview and Focus Group Discussion. Data analysis was constructed using Mario Diani’s theory about social movement as a network. The result of research shows that the first factor is the emergence of problem and grievance about river contamination by rubbish and waste due to people’s poor literacy about river. The second one is movement strategy and tactic used in the form of structural and cultural approach to restore the river. The third is the process of creating social network based on shared idea, value, norm, collective identity, and interest related to the river. The fourth is social network experiencing transformation from spontaneity, institutionalization to autonomy phase as the attempt of adapting to and reconciling with the form of change to maintain the movement sustainability. Keywords: River Restoration Movement, Movement Strategy, Social Network Establishment, and Social Network Transformation